MEMAHAMI BERGERILYA LEWAT KOMUNIKASI PEMASARAN - Bayquni, Bayquni (Universitas Prof. Dr. Moestopo (Beragama), 2010)
Marketing communications is a strategic way to increase sales. However, not only until the Purchase or intention to buy just the marketing communication is possible, even the values contained in a product to the value required by the consumer could happen, so consumers no longer buy products diam buy a brand but also had to buy value. Thus when designing marketing communications strategies that build has perfect accuracy and carefulness both in its determination of the marketing mix (Product, Price, promotion and place) or in its selection of promotion mix (Personal selling, Direct Marketing, PR and Publicity, Sales Promotion, Packaging, and Word Of Mouth (WOM)) then berhasil pula marketing communications activities undertaken. In this paper we will study how to make the precision and accuracy in using marketing communications, better known by the name of integrated marketing communications (Integrated Marekting Communication). Because marketing is very heavy with the name of competition or in the